2017
DOI: 10.7324/rjc.2017.1041866
|View full text |Cite
|
Sign up to set email alerts
|

TERMITICIDAL ACTIVITY OF Toona sinensis WOOD VINEGAR AGAINST Coptotermes curvignathusHolmgren

Abstract: Termiticidal activity of wood vinegar from Toona sinensis (TS) sawdust has been evaluated against Coptotermes curvignathus. TS wood vinegar was produced at 250-300°C pyrolysis temperature, and a no-choice test was applied for evaluating termiticidal activity with thirty-three active termites. The concentrations of TS wood vinegar in the dried filter paper was prepared to 0% (solvent only), 2%, 4%, 6%, and 8%. The TS wood vinegar showed strong termiticidal activity and that concentrations of wood vinegar signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Asap cair (liquid smoke) merupakan teknologi konversi biomassa melalui penguraian senyawa kimia organik menjadi senyawa penyusunnya (Ardila, Thamrin, WS, & Eddiyanto, 2013). Produksi asap cair pada umumnya menggunakan teknik pirolisis (Adfa et al, 2017;Pimenta, Fasciotti, Monteiro, & Lima, 2018;Yang, Yang, Liang, Gao, & Wu, 2016), dimana biomassa dipanaskan lebih dari 300°C (A'yuni, Darmadji, & Pranoto, 2017) sampai 450°C (Pimenta et al, 2018), dan asap dikondensasi menjadi bentuk cairan (Adfa et al, 2017;Ardila et al, 2013;Yang et al, 2016). Teknologi ini merupakan teknologi ramah lingkungan (Ariyani, Mujiyanti, & Harlianto, 2015;Wijaya, Wiharto, & Anwar, 2018) yang dapat mengurangi pelepasan CO 2 ke udara.…”
Section: Pendahuluanunclassified
“…Asap cair (liquid smoke) merupakan teknologi konversi biomassa melalui penguraian senyawa kimia organik menjadi senyawa penyusunnya (Ardila, Thamrin, WS, & Eddiyanto, 2013). Produksi asap cair pada umumnya menggunakan teknik pirolisis (Adfa et al, 2017;Pimenta, Fasciotti, Monteiro, & Lima, 2018;Yang, Yang, Liang, Gao, & Wu, 2016), dimana biomassa dipanaskan lebih dari 300°C (A'yuni, Darmadji, & Pranoto, 2017) sampai 450°C (Pimenta et al, 2018), dan asap dikondensasi menjadi bentuk cairan (Adfa et al, 2017;Ardila et al, 2013;Yang et al, 2016). Teknologi ini merupakan teknologi ramah lingkungan (Ariyani, Mujiyanti, & Harlianto, 2015;Wijaya, Wiharto, & Anwar, 2018) yang dapat mengurangi pelepasan CO 2 ke udara.…”
Section: Pendahuluanunclassified
“…Raw materials such as wood or biomass to manufacture liquid smoke contain the main components as cellulose, hemicellulose, and lignin (Kan et al 2016). Some researchers have reported that liquid smoke can be used as an anti-termite (Adfa et al 2017;Indrayani et al 2012;Oramahi et al 2014), antifungal (Adfa et al 2020;Oramahi and Yoshimura 2013;Subekti and Yoshimura 2020), and insect repellents (Prabowo et al 2016;Sapindal et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several plants have been reported to have natural compounds that possessed as insecticide features. Toona sinensis L. (Meliaceae) with the common name of Chinese mahogany, Chinese toon or red toon, is native to eastern and southeastern Asia from North Korea, China, Nepal, India, Myanmar, Thailand, Malaysia up to Indonesia (Adfa et al, 2017). Extract fresh leaves contained a high amount of sesquiterpenes, including copaene, β-caryophyllene, caryophyllene, β-eudesmene and the compounds showed antimicrobial activity against Staphylococcus aureus (Wang et al, 2014) and Captotermes cunvignathus on woods (Adfa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%